Formação de professores de língua inglesa e a pedagogia dos multiletramentos: ensino para tempos digitais - Marilane de Abreu Lima Miranda (2020)
Continuing teacher education in Brazil is essential for educators’ critical reflections about their educational domain since they are often distant from academic centers where they could update their knowledge regarding the latest teaching/ learning theories and corresponding practices. Additionally, they often face great challenges in their local educational contexts. Although supported by the Board of Education of Minas Gerais, continuing education courses for English teachers in the state public schools are still scarce. Besides, the level of difficulties doubles for those who do not have available time for constructing critical theoretical and practical knowledge to transform their practices. This research analyzes data from a continuing education course that was given to English teachers from a state administrative institution, the Regional Superintendence of Teaching of Ponte Nova in Minas Gerais, that includes 17 municipalities. It was planned to be online to reach all the teachers from 70 different schools and implemented through customized tasks that were solidly supported by recent studies on language and technology. The main objective was to investigate whether or not the proposed continuing education for English teachers contributes to their new roles, that of transformative educators. Different from other research studies that consider only the theory of multiliteracies, this investigation is also supported by the cyclical knowledge processes of the multiliteracies pedagogy that includes assumptions of the critical literacy, associated with Bloom's digital taxonomy and its cognitive learning objectives, augmented by the pedagogical use of available free digital tools. The method used for this investigation was the case study considering the qualitative paradigm. The data were collected through the responses to the customized tasks given by the participants during the continuing teacher education course, the lesson plans elaborated by them and from 2 questionnaires - one applied at the end of the course and the other, one year after it was over. The analysis is supported by aspects coming from our critical use of the references: the tenets of the theory of multiliteracies, the principles of the knowledge processes of the multiliteracies pedagogy, associated with Bloom's digital taxonomy and contributions from the pedagogical use of digital tools. The results reveal that the continuing education for English teachers investigated and analyzed in this study provided participants with critical and reflexive theoretical and methodological support for the enhancement of their knowledge on multiliteracies. Further, the lesson plans developed by them showed that they constructed meaning in a reflexive and critical way and implemented what they learned during the course, including the pedagogical use of digital tools. The answers to the first questionnaire revealed that they were aware of the benefits of the continuing teacher education through the CFPM to the critical and reflexive ways they view their educational mission as English teachers now. The data from the second questionnaire, applied one year after the research was over, revealed that they were applying creatively what they have learned in their teaching contexts.